A263 MICE CHALLENGED WITH DNBS FOUR DAYS AFTER INFECTION WITH THE RAT TAPEWORM HYMENOLEPIS DIMINUTA ARE PROTECTED FROM COLITIS. (26th February 2020) - Li, S; Wang, A; McKay, D M
Abstract: Background: Helminth therapy for colitis is supported by data from murine models, including infection with H. diminuta inhibiting dinitrobenzene sulphonic-acid (DNBS)-induced colitis. Considering H. diminuta as a candidate helminth therapy the kinetics of infection in the context of inflammation should be addressed. Reciprocally, it is important to know if colitis alters the immune response to the helminth. Aims: 1) Assess DNBS-colitis in mice infected 4-days previously with H. diminuta . 2) Determine in DNBS-induced colitis affects the outcome of infection with H. diminuta . Methods: Male BALB/c mice were infected by gavage with five H. diminuta and four days later were challenged with DNBS (3 mg, ir.). Disease was assessed 3 days later (i.e. day 7-post H. diminuta) by colon length, disease activity score and histopathology (n=9–14 mice, 3 experiments). Alternatively, on day three post-DNBS, mice were infected with H. diminuta and worm infectivity and splenocyte Th2-cytokine production assessed at 8 days post-infection (n=5–9 mice, 1 experiment). Results: Mice challenged with DNBS at 4-days post-infection were significantly protected from colitis, with 2/14 mice requiring humane euthanization for disease severity compared to 6/13 in the DNBS-only group. Splenocyte production of IL-4, IL-5 and IL-10 was increased in the H. diminuta -only group compared to control mice: DNBS-only treated mice showed reduced levels of all three cytokines and H. diminuta +DNBS mice had cytokine levels not different from H. diminuta -only infected mice. DNBS-colitis prior to infection did not affect the increase in systemic TH2 immunity evoked by H. diminuta, but did result in greater intestinal worm burdens. Conclusions: The data suggest (1) the window of opportunity for H. diminuta to suppress colitis in a prophylactic regimen is at least 4–8 days post-infection, and (2) H. diminuta administered to mice at the peak of colitis severity mobilizes TH2 immunity that could promote quicker recovery from colitis. Funding Agencies: CAG, CCC, NRCNSERC